Service Quality, Interest Rate, and Deposit On Call On Profitability (Study in Bank Mandiri Branch Office in PT. X) - Renny Sunarny; Ellen Rusliati (TRIKONOMIKA, 2016)
The aim of this research is to measure the influence of service quality and interest rate on deposit on call, and the influence of service quality, interest rate, and deposit on call on profitability. Hopefully, the result could give contributions for the development of management study, especially financial management. It also could hopefully provide valuable information about the importance of service quality, interest rate, and deposit on call in order to increase bank profitability. The location of this research was in Bank Mandiri, Bandung Branch Office in PT. X. The methodology used was quantitative research using descriptive and verificative analysis. Research data horizon was cross sectional using path analysis method. The results showed that there were significant influence between the interest rate on deposit on call, and service quality, interest rate, and deposit on call to profitability. It was found also that the influence of straight interest rate on profitability was weaker than interest rate on profitability via deposit on call.